Distinct pattern of TP53 mutations in human immunodeficiency virus–related head and neck squamous cell carcinoma. Issue 1 (20th October 2017) - Gleber‐Netto, Frederico O.; Zhao, Mei; Trivedi, Sanchit; Wang, Jiping; Jasser, Samar; McDowell, Christina; Kadara, Humam; Zhang, Jiexin; Wang, Jing; William, William N.; Lee, J. Jack; Nguyen, Minh Ly; et al.
Abstract : BACKGROUND: Human immunodeficiency virus–infected individuals (HIVIIs) have a higher incidence of head and neck squamous cell carcinoma (HNSCC), and clinical and histopathological differences have been observed in their tumors in comparison with those of HNSCC patients without a human immunodeficiency virus (HIV) infection. The reasons for these differences are not clear, and molecular differences between HIV‐related HNSCC and non–HIV‐related HNSCC may exist. This study compared the mutational patterns of HIV‐related HNSCC and non–HIV‐related HNSCC. METHODS: The DNA of 20 samples of HIV‐related HNSCCs and 32 samples of non–HIV‐related HNSCCs was sequenced. DNA libraries covering exons of 18 genes frequently mutated in HNSCC ( AJUBA, CASP8, CCND1, CDKN2A, EGFR, FAT1, FBXW7, HLA‐A, HRAS, KEAP1, NFE2L2, NOTCH1, NOTCH2, NSD1, PIK3CA, TGFBR2, TP53, and TP63 ) were prepared and sequenced on an Ion Personal Genome Machine sequencer. DNA sequencing data were analyzed with Ion Reporter software. The human papillomavirus (HPV) status of the tumor samples was assessed with in situ hybridization, the MassARRAY HPV multiplex polymerase chain reaction assay, and p16 immunostaining. Mutation calls were compared among the studied groups. RESULTS: HIV‐related HNSCC revealed a distinct pattern of mutations in comparison with non–HIV‐related HNSCC. TP53 mutation frequencies were significantly lower in HIV‐related HNSCC. Mutations in HIV+ patients tended to be TpC>T nucleotide changes for all mutated genes but especially for TP53 . CONCLUSIONS: HNSCC in HIVIIs presents a distinct pattern of genetic mutations, particularly in the TP53 gene. HIV‐related HNSCC may have a distinct biology, and an effect of the HIV virus on the pathogenesis of these tumors should not be ruled out. Cancer 2018;124:84‐94 . © 2017 American Cancer Society . Abstract : Head and neck squamous cell carcinoma in patients infected with human immunodeficiency virus (HIV) shows a specific pattern of DNA mutations in comparison with head and neck squamous cell carcinoma in non–HIV‐infected individuals. This is particularly true for mutations in TP53 : tumors from HIV‐infected patients show a virus‐related mutation fingerprint, regardless of any human papillomavirus co‐infection. See also pages 14‐17.